IMPLEMENTASI SANITATION STANDARD OPERATING PROCEDURE (SSOP) PADA PROSES PEMBEKUAN IKAN KAKATUA (STANIS FRENALIS) DI PT. PERIKANAN INDONESIA UNIT PENGOLAHAN IKAN KABUPATEN SIMEULUE - Yuni Sartika Amiria; Anhar Rozi Rozi (JURNAL PERIKANAN TROPIS, 2022)
As marine products known as the products that easily experience quality degradation, they need good handling and processing according to SSOP requirements to slow down the enzymes and pathogenic bacteria activity. This research was conducted at PT. Perikanan Indonesia, Simeulue Regency. On 27 August to 27 November 2021. This study aims to evaluate the application of SSOP frozen parrot fish production at PT. Indonesian Fisheries, Simeulue District. This study used descriptive qualitative method. Data was collected using observation, interviews, active participation and documentation. Some of the SSOP requirements on the frosting process of freezing parrotfish at PT. Perikanan Indonesia had been fulfilled, but there were several obstacles in the application of personal hygiene and sanitation of processing rooms. This can cause product contamination.Keywords: Implementation of SSOP, Frosting, Parrotfish